Salesforce B2C Solution Architect's Handbook - King, Mike (Packt Publishing, 2021)
Master the skills you need as a Salesforce B2C Solution Architect to design an optimized business-to-consumer (B2C) solution across the Salesforce Customer 360 ecosystem, including B2C Commerce, Service Cloud, and Marketing Cloud Key Features Create a unified view of the customer across Salesforce products and beyond Avoid inefficiencies and costly rework caused by poor architectural designs Prepare for the B2C Solution Architect exam and Salesforce certification with practical scenarios following Salesforce best practices Book Description A carefully designed Customer 360 solution spanning B2C Commerce, Marketing Cloud, and Service Cloud provides the foundation for a single view of the customer, unique insights, and transformational capabilities. There is currently a huge demand in the marketplace for professionals who understand how to leverage these components together. Salesforce B2C Solution Architect's Handbook will help you understand the integration options and products that help you deliver value for organizations. You'll start by developing a solid understanding of the capabilities of each component in the Customer 360 ecosystem, their data models, and governance. As you progress, you'll explore the role of a B2C solution architect in planning critical requirements and implementation sequences to avoid costly rework. The book will also guide you through the options for integrating products with the Salesforce ecosystem and demonstrate best practices for data modeling across Salesforce products and beyond. Once you have the core knowledge required to be a successful solution architect, you'll learn about tools, techniques, and certification scenarios in preparation for the B2C Solution Architect exam. By the end of this book, you'll have the skills to design scalable, secure, and future-proof solutions supporting your customers' critical business demands. What you will learn Explore key Customer 360 products and their integration options Choose the optimum integration architecture to unify data and experiences Architect a single view of the customer to support service, marketing, and commerce Plan for critical requirements, design decisions, and implementation sequences to avoid sub-optimal solutions Integrate Customer 360 solutions into a single-source-of-truth solution such as a master data model Support business needs that require functionality from more than one component by orchestrating data and user flows Who this book is for T...